Identity Crisis: Alienation and Religious Demarcation in Bhisham Sahni’s Pali - Subedi, Bhim Prasad (Journal of Development Review, 2023)
Bhisham Sahni’s "Pali" the novel, delves into the devastating fallout of the Indian-Pakistani split and emphasizes the severe suffering brought on by religious enmity. Pali the protagonist of the novel a representative of solitude and melancholy, moves through a range of feelings, from solitary to identity-crisis. This research highlights the wider impact of religious prejudice and parallels the suffering of individuals caught in the crossfire. The narrative, which is linked with contemporary partition literature, reveals common trauma and its lingering effects. Pali’s anguish highlights the universal narrative of suffering and reveals the pervasive effects of hatred. Despite Sahni’s efforts to link experience and understanding, some agonies are still indescribable. The anguish that Pali, the main character, endured resides imprisoned, scorched too deeply for words. The book serves as a conduit for these profound effects, reflecting inexpressible sentiments. Pali encapsulates generational trauma, testifying to the religious enmity that birthed the India-Pakistan division. Pali’s journey unfolds into a tapestry of emotions, revealing identity’s complexity, coexistence’s fragility, and prejudice’s destructiveness. Sahni’s work transcends his works portraying humanity’s spirit, historical shadows, and a call for harmony amidst discord. This research revitalizes "Pali," its resonance reaching those seeking to comprehend the past and shape an inclusive, empathetic future.